Simulation of Extreme Arctic Cyclones in IPCC AR5 Experiments - Vavrus, Stephen (2012)
The primary goals of this project are to assess the ability of the current generation of global climate models (GCMs) to simulate extreme Arctic cyclones and identify changes in the characteristics of these storms caused by greenhouse-forced climate change to present. These goals are being addressed through the following questions. First, how realistically does the widely used CCSM4 GCM simulate the observed characteristics of extreme Arctic cyclones and how sensitive are these events to the horizontal resolution of the model? Second, do other GCMs generate such storms and, if so, are there any common characteristics among models that successfully do so? Third, does the preferred location of these systems and their impacts shift as the cyclogenetic baroclinic zone induced by the sea ice margin migrates poleward with time? Fourth, what do these state-of-the-art climate models suggest about changes in the frequency vs. intensity of extreme Arctic cyclones? The original document contains color images.